Modeling and Simulation study on Cement Raw Mill Process Control - Hisbullah Hisbullah; Azwar Azwar; Rahmadin Rahmadin; Hasan Rahmat; Abubakar Abubakar (Journal of Applied Technology, 2022)
The composition of oxides in cement raw materials tends to be unstable depending on the location where the raw materials are taken. Changes in the composition of these raw materials affect the performance of the control system on the raw mill. In this study, the modeling and simulation of the Raw Mill unit control algorithm for changes in the oxide composition of raw materials is studied. This modeling is carried out to see the performance of the control system on changes in the composition of raw materials. This study aims to develop a raw mix control algorithm and test its performance when the data for the analysis of the oxide composition is not available. The research method used is a simulation study using MATLAB software, namely: (1) Creating a mathematical model regarding the incoming mass flow rate from the raw mill; (2) Running a simulation of the raw mill inlet mass flow rate process; and (3) Testing the performance of the control algorithm in overcoming the problem of lack of data. analysis of oxide composition in raw materials with scenarios that include processes with fixed setpoints and changing setpoints. The results showed that the raw mix design control algorithm can only control the raw meal parameters if the data for the analysis of the oxide composition is available. With these results, the control algorithm for the raw mill control process needs to be modified in order to maintain the raw meal parameters when the oxide composition analysis data is not available.